STUDI LITERATUR PENGARUH PARAMETER PENGELASAN TERHADAP SIFAT FISIK DAN MEKANIK PADA LAS TITIK (RESISTANCE SPOT WELDING) - Haikal, Haikal; Triyono, Triyono (ROTASI, 2013)
Resistance spot welding (RSW) is the most widely used for joining thin sheet metals in automotive industry. Various applications of dissimilar materials and thicknesses were commonly found in many spot welding processes especially in the manufacture of car body. The resistance spot welding of dissimilar materials are generally more challenge than similar materials due to differences in the physical, chemical, and mechanical properties of the base metals. Differences of materials have an impact on heat input generated at the spot welding. Diameter of the weld nugget size is influenced by several parameters such as electric current, welding time, different types of material, and the thickness of the plate. Nugget diameter will influence on physical and mechanical properties weld such as microstructure, shear strength and hardness. For practical use, various industrial standards have recommended a minimum weld size for a given sheet thickness, mostly in the form of tables. For example the American Welding Society (AWS), Society of Automotive Engineering (SAE) and the American National Standards Institute (ANSI). They were only suitable to be apllied on the similar metal and thickness joint because in this joint, symetrical nugget will be formed. Meanwhile a type of dissimilar metal that joined by spot welding method will result in the asymetrical nugget. This paper aims to review the results of researchs on the similar and dissimilar resistance spot welded joint to evaluate the use of similar metals weld parameters and standards on the dissimilar metals weld. It was determined that parameters welding such as electric current, welding time, and the standard for similar metals weld can not be applied on the dissimilar metals weld. The asymetrical nugget shape decreased shear strength on the weld nugget. The most important factor that was considered on the dissimilar metals weld to make high quality weld joint was nugget diameter. If the nugget diameter weld increased the strength of welding will increase.